Posterior urethral valves and Cowper's syringocele: A rare association causing voiding dysfunction - K V Satish Kumar; Abraham Mammen; Aneez A Ratani; Karthikeya K Varma (Wolters Kluwer Medknow Publications, 2012)
Urethral syringoceles are cystic dilatations of paired bulbourethral glands of Cowper. They can cause voiding dysfunction in male children and usually occur in isolation. We report a rare association of Cowper's syringocele with posterior urethral valves in a 4-year-old child, which was successfully managed endoscopically.